CONTRIBUTION OF HOTEL WEBSITE, ONLINE TRAVEL AGENT, AND OFFLINE TRAVEL AGENT TO ROOM REVENUE IN MELIA BALI - Nida Ulhasanah Dwi Sulistyaningrum; I Gede Mudana; I Ketut Astawa; Made Sudiarta; Ni Luh Eka Armoni (Politeknik Negeri Bali, 2019)
This research is about the contribution of each distribution channel towards room revenue in Melia Bali. The purpose of this research is to find out the contribution of hotel website, online travel agent, and offline travel agent towards room revenue at Melia Bali during 2015-2017. Data are collected in this research through interview, observation, and literature study. Data analysis method used is descriptive statistics. The result of the research shows that the biggest contribution of the distribution channel is offline travel agent. While the other distribution channels are having a fluctuations issue, where in year 2015 and 2016 the online travel agent distribution channels is higher than the hotel website. But in 2017, the hotel website has bigger contribution than online travel agents. The average contribution of hotel website towards room revenue in 2015-2017 is 17.03%. The distribution channel of online travel agent is 16.83% and the other five online travel agents that have the most contribution upon room revenue of Melia Bali in 2015-2017 are booking.com, Expedia, Agoda, Hotelbeds, and Orbitz. Contribution on distribution channel of offline travel agent is 66.15% and the five offline travel agents that have the most contribution towards room revenue of Melia Bali in 2015-2017 are Flight Center, TUI Deutschland, Meier's Weltreisen, TMS Tours, and HIS Bali Tours and Travel.